A3.29 Micro-RNA molecules are clearly involved in pathogenesis of idiopathic inflammatory myopathy. (31st January 2014) - Remakova, Martina; Skoda, Marek; Faustova, Marketa; Plestilova, Lenka; Mann, Herman; Novota, Peter; Vencovsky, Jiri
Abstract : Background and Objectives: MicroRNAs can regulate the gene expression and cellular functions such as cell cycle, differentiation, or apoptosis. Emerging evidence has demonstrated that miRNAs play a vital role also in the regulation of immunological functions, including the development of autoimmunity. Like in most of other autoimmune diseases, the etiopathogenesis of Idiopathic inflammatory myopathy (IIM) is also believed to be triggered by environmental factors in combination with susceptible genetic background. Beside a genetic risk located within the MHC complex, the role of epigenetic regulations including changes in miRNAs expression profiles in autoimmunity development have recently also been implicated. The aim of this study was to look for specific miRNA expression patterns in the serum, peripheral blood mononuclear cells (PBMCs) and muscle biopsies of patients suffering from idiopathic inflammatory myopathy. Materials and Methods: RNA was isolated from serum, PBMCs and muscle biopsy samples of patients suffering from IIM using modified Trizol-chloroform method. The expression profile of miRNAs was determined by 60K high density microarray from Agilent Company. Results: In total, 87 miRNAs were found to be differentially expressed at a significant level (p<0.05) in serum samples of patients with IIM. Under the same conditions for comparison, 14 miRNAs were differentially expressed in PBMCs (p<0.05) and 78 miRNAs in muscle biopsies (p<0.05). What more, the expression of 10 miRNA molecules have shown the same expression regulation among either serum and muscle biopsy, or PBMCs and muscle biopsy samples. Nine of them were upregulated in serum and muscle biopsy samples; one of them was upregulated in PBMCs and biopsy samples. Beside this concordance, we could see significant differences in expression between patients and controls in all of these 10 miRNA molecules (p<0.05). Conclusions: This is the first study providing information about complete expression profile of miRNA molecules found in the serum, PBMCs and muscle biopsy samples of patients with IIM. We have found that a number of miRNAs were differentially expressed in diverse tissue samples indicating tissue specific expression of miRNAs. The "missregulated" miRNAs might potentially act as biomarkers of initiated systemic inflammatory response, or functional molecules related to muscle tissue injury, or molecules involved in regulation of immune response. Acknowledgement: This study was supported by the Internal Grant Agency of the Ministry of Health in the Czech Republic [MZČR NT 12452-4], Institutional support of MHCR VZ (00023728) and The Charles University Grant Agency (No.621812).